Deinstitutionalization of the child care system in Lithuania - Pivoriene, Jolanta (International Journal of Child, Youth and Family Studies, 2020)
The reform of the child care system in Lithuania started with the Ministry of Social Security and Labor approving the Strategic Guidelines for Deinstitutionalization in 2012, followed by the Transition from Institutional Care to Community-Based Services in 2014. The strategic aim of the reform was to create a system including a comprehensive range of services that would enable every child and their family or guardians to receive individual services as well as community assistance according to their needs. The process of transformation of institutional care was designed in two steps: creation of the necessary conditions for the transformation, which took place in 2014 to 2017, and development of infrastructure in the regions, planned for 2017 to 2020, but now extended to 2023. The goal of this article is to discuss the deinstitutionalization process by presenting legal regulations, information about the conceptualization and scope of the project, and evidence based on documents and statistical and secondary data analysis. I will also discuss possible contradictions between analytical and political discourses, and quantitative and qualitative evidence.